2018
DOI: 10.1155/2018/6042602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Valorization of Derivatives of 4-Phenyl-1,5-Benzodiazepin-2-One

Abstract: The objective of our work is to make a pharmacological study of molecules derived from 4-phenyl-1,5-benzodiazepin-2-one carrying long chains so that they have a structure similar to surfactants, with the benzodiazepine as a hydrophilic head and a carbon chain as a hydrophobic tail. First, we studied the acute toxicity of the above mentioned 4-phenyl-1,5-benzodiazepin-2-one derivatives. This study was conducted according to OECD 423 guidelines in female mice and revealed that these compounds are nontoxic. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…We also note that the activity of 5a-d chemicals decreases as the alkyl chain increases. ese results confirm our previous work [10], in which we have shown that the addition of an alkyl chain to molecule 3 increases its pharmacological activity, and that this activity decreases as the alkyl chain increases. All results at 50 and 100 mg/kg confirm that some benzodiazepines can be used as analgesics.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also note that the activity of 5a-d chemicals decreases as the alkyl chain increases. ese results confirm our previous work [10], in which we have shown that the addition of an alkyl chain to molecule 3 increases its pharmacological activity, and that this activity decreases as the alkyl chain increases. All results at 50 and 100 mg/kg confirm that some benzodiazepines can be used as analgesics.…”
Section: Discussionsupporting
confidence: 91%
“…e spectral data for the identification of these compounds are presented in our previous publication [10]. (20-30 g) and rats Wistar adults were used in the work.…”
Section: Synthesis Of 4-phenyl-15-benzodiazepin-2-one and Itsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they belong to the category V of the Globally Harmonized System (GHS). These results corroborate those of our previous work in which we have shown that the insertion of long alkyl chains on 4-phenyl-1,5-benzodiazepin-2-one leads to nontoxic products [53]. The literature also mentions a large number of studies showing the absence of toxicity on molecules with long carbon chains [5456].…”
Section: Discussionsupporting
confidence: 91%